Evaluation of thiol/disulphide homeostasis as a novel predictor testing tool of early pregnancy viability - Hatice Akkaya; Gülsüm Uysal; Barış Büke; Gamze Gök; Özcan Erel; Çiğdem Karakükçü (Elsevier, 2018)
Objective: To evaluate serum dynamic thiol/disulphide concentrations in patients with suspected missed abortion (MA) and to determine whether this ratio has a predictive role in the viability in these pregnancies. Materials and Methods: In this prospective cohort study, 48 out of 120 recruited pregnant patients were confirmed MA in the study group. Following the recommended waiting time (7-10 days), the remaining 72 viable pregnancies that met the inclusion criteria were categorized as the control group. A novel, automated, and spectrophotometric assay, which can measure both sides of the thiol/disulphide balance, was used. The cut-off values were used for the ROC curve. Results: There were no statistically significant differences between the groups (MA and control) regarding maternal obstetric and demographic features. Significantly reduced levels of Total Thiol and Native Thiol were shown in patients with MA compared to the control group (p = 0.016 and p = 0.001, respectively). Serum levels of disulphide was significantly increased in the MA group (23.4 ± 7.8 μmol/l vs. 17.9 ± 4.99 μmol/l, p < 0.0001). Disulphide values of less than 17.68 predicted 80.8% of the viable pregnancies. Conclusion: Significantly increased serum disulphide levels, one of the oxidative stress markers, and decreased antioxidant levels (total and native thiol) were found in patients with MA. Increased oxidative stress status is thought to play a role in the etiology of MA. Serum dynamic thiol/disulphide homeostasis may serve as a promising testing tool to rule out subsequent diagnosis of MA and may benefit as an early pre-treatment testing tool for viability.